2013
DOI: 10.7717/peerj.38
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Emotiv EPOC®EEG gaming system for measuring research quality auditory ERPs

Abstract: Background. Auditory event-related potentials (ERPs) have proved useful in investigating the role of auditory processing in cognitive disorders such as developmental dyslexia, specific language impairment (SLI), attention deficit hyperactivity disorder (ADHD), schizophrenia, and autism. However, laboratory recordings of auditory ERPs can be lengthy, uncomfortable, or threatening for some participants – particularly children. Recently, a commercial gaming electroencephalography (EEG) system has been developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
236
4
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(265 citation statements)
references
References 20 publications
13
236
4
12
Order By: Relevance
“…Laboratory data using a mobile electroencephalography (EEG) headset (Emotiv EPOC+; validated for both laboratory and outdoor settings [17,18]) showed outputs that corresponded with self-reported measures on attractiveness, willingness to visit, valence and arousal of static images of landscapes or urban scenes [19]. This study used data from the Affectiv Suite, Emotiv proprietary software, which analyzes EEG from distinct brain activity patterns and allocates a label defining an emotional parameter ('frustration', 'excitement', 'engagement', 'meditation', 'long term excitement').…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory data using a mobile electroencephalography (EEG) headset (Emotiv EPOC+; validated for both laboratory and outdoor settings [17,18]) showed outputs that corresponded with self-reported measures on attractiveness, willingness to visit, valence and arousal of static images of landscapes or urban scenes [19]. This study used data from the Affectiv Suite, Emotiv proprietary software, which analyzes EEG from distinct brain activity patterns and allocates a label defining an emotional parameter ('frustration', 'excitement', 'engagement', 'meditation', 'long term excitement').…”
Section: Introductionmentioning
confidence: 99%
“…The marker circuit has been proven to successfully record auditory evoked potentials on human subjects [4]. The audio stimuli were based on the ramp tone.…”
Section: Resultsmentioning
confidence: 99%
“…An auditory evoked potential study using this circuit has been conducted by Badcock et al [4] where the EPOC accompanied by the marker circuit was validated against Neuroscan. Section II describes the circuit to convert the audio signal from the headphone output to a pulse that can be fed to a pair of the EEG channels and the methods to verify the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Badcock et al. [1] simultaneously recorded, using research and Emotiv Epoc devices, the EEG of 21 subjects while they were presented with 566 standard (1000 Hz) and 100 deviant (1200 Hz) tones under passive and active conditions. For each subject, they calculated auditory ERPs (P1, N1, P2, N2, and P300 peaks) as well as mismatch negativity (MMN) in both active and passive listening conditions.…”
Section: Related Workmentioning
confidence: 99%
“…They are mainly marketed as gaming devices and provide a limited solution to the expensive equipment problems described above: they are wirelessly connected to an ordinary computer, 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 they require a short set-up time to adjust the electrodes to the user's scalp, and they do not require conductive gel. Recent research on evaluating the reliability of some of these low-cost EEG devices for research purposes has suggested that they are reliable for measuring visual and auditory evoked potentials [Duvinage, 2013;Debener, 2012;Badcock, 2013].…”
mentioning
confidence: 99%